Security Zone and Key Derivation Management in Centralized Security Control in Wimax Multihop Relay System - Adnan, Shahid Khan; N., Fisal; N.N.M.I., Ma’arof; Fath.E.I., Khalifa; M., Abbas; Hashim, E. A. Elshafie (2010)
A wireless internet services are rapidly expanding and improving, it’s important to provide users with not only high speed and high quality wireless service but also secured. Mesh networking support was added for improved coverage and throughput. A WiMAX mesh network not only increases the wireless coverage but a so provides features such as lower backhaul deployment cost, easy setup and deployment, robustness and reconfigurability, which make it one of the indispensabl technologies in next generation wireless network. In order to operate efficiently, communication must be scheduled either by a distributed, centralized or hybrid algorithms. A WiMAX network usually operates in a highly dynamic and open environment therefore it is known to be more vulnerable to security holes. In this paper, we give a detailed overview of privacy key management protocol (PKM) and key derivation management in centralized security zone control in a multihop relay system. Here we also try to discuss the trade offs of centralized and distributed security zones and key management in multihop relay system.